FROM PASSION TO PROFIT: AN ANALYSIS OF ENTREPRENEURIAL MANAGEMENT STRATEGIES IN SCALING LOCAL COFFEE SHOP CREATIVE-PRENEURSHIP - Wijaya Wijaya; Napat Chai; Jamil Khan; Abdullah Abdullah (Journal of Social Entrepreneurship and Creative Technology, 2025)
The rise of creative-preneurship in the local coffee sector, exemplified in Indonesia, presents a critical managerial challenge: the transition from passion-driven ventures to scalable, profitable enterprises. Many founders fail to navigate this “passion-to-profit” transition, often due to a “founder-centric bottleneck.” This study aims to identify, analyze, and model the effective entrepreneurial management strategies that differentiate high-growth, creative-led coffee shops from low-growth or stagnant ventures. A convergent parallel mixed-methods design was employed, analyzing a purposive sample of 30 Indonesian coffee shops. This involved a comparative analysis of high-growth (N=15) and low-growth (N=15) ventures using quantitative financial and operational surveys and 45 in-depth, semi-structured interviews. Quantitative findings reveal a stark divergence: high-growth firms averaged 45.2% CAGR and 25.1% employee turnover, versus 6.1% CAGR and 78.4% turnover for low-growth firms. Qualitative analysis identified “Formalized Creative Systems” and “Decentralized Leadership” as key success strategies. Inferential analysis confirmed “Formalized Creative Systems” as the strongest predictor of successful scaling (β = 2.14, p < 0.01). Scaling a creative-preneurial venture is contingent upon the founder’s ability to systematize their creative vision. This research provides the Scalable Creative-preneurship Framework (SCF), an empirically-validated model for resolving the “art-commerce” paradox.